Perang Ekuador dan Peru Tahun 1995: Analisis Democratic Peace Theory - Ahmad Daniel Kusumah Anshary (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
This study tries to explain the reasons why Peru and Ecuador went to war with each other in 1995, even though both are democracies. The research was conducted concerning Immanuel Kant's Democratic Peace Theory by examining norms and institutions as essential factors in developing his theory. This study uses qualitative research with literature review and interview methods. The study will focus on the conditions of norms and institutions in Peru and Ecuador in 1995, the year the two countries decided to go to war with each other. Based on the research results, it is known that democratic norms and institutions owned by Ecuador and Peru have not been able to create peace as has been assumed by Immanuel Kant in the Democratic Peace Theory. Although Ecuador has democratic institutions that can reduce the authority of its leaders in decision-making, the domestic democratic norms established in the 1830 Constitutional Law cannot make the Ecuadorian people's support refer to peace in overcoming the Cenepa border conflict. On the contrary, in Peru, democratic norms that prefer to negotiate and make peace are not followed by the effectiveness of the role of democratic institutions that cannot limit President Fujimori's authority, who chooses to carry out attacks in border areas which then triggers a war.